Richness for Tumor-Infiltrating B-Cells in the Oral Cancer Tumor Microenvironment Is a Prognostic Factor in Early-Stage Disease and Improves Outcome in Advanced-Stage Disease - Nauta, Irene H.; Nijenhuis, Dennis N. L. M.; Ganzevles, Sonja H.; Raaff, Pamela I.; Kloosterman, Jan; Bloemena, Elisabeth; Brakenhoff, Ruud H.; Leemans, C. René; van de Ven, Rieneke (Cancers, 2025)
Background/Objectives: Most studies on the interaction between the immune system and cancer focus on T-cells, whereas studies on tumor-infiltrating B-lymphocytes (TIL-Bs) are still underrepresented. The aim of this study was to assess the prognostic impact of TIL-Bs in early- and advanced-stage oral cavity squamous cell carcinoma (OCSCC). Methods: In total, 222 OCSCCs were studied. Consecutive sections were stained for CD45 and CD19. OCSCCs were categorized as either “TIL-B-rich” or “TIL-B-poor”, and the survival of both groups was analyzed. Similar analyses were performed for CD45+ TILs and the CD19/CD45 ratio. Matched subgroups of twelve TIL-B-rich and TIL-B-poor tumors were stained for CD3 and CD8 to determine differences in T-cell infiltration, and further spatial interaction between T- and B-cells was evaluated in six samples. Results: Five-year OS was 75.0% for TIL-B-rich and 54.2% for TIL-B-poor OCSCCs (p < 0.001). The survival benefit of TIL-B-rich OCSCCs remained significant after correction for the histopathological characteristics (p = 0.033). While for early-stage tumors, TIL-B richness benefited OS independent of demographic-, clinical, or histopathological features, for advanced-stage disease, this was not the case, although a clear benefit of a TIL-B-rich status was observed, specifically up until 36 months after diagnosis. TIL-B-rich tumors contained more CD3+ TILs (p = 0.007), but not CD8+ TILs. Spatial characterization suggested that TIL-Bs mostly co-localized with CD3+CD8− TILs and that this interaction was increased in TIL-B-rich OCSCC. Conclusions: The presence of TIL-Bs is associated with a more favorable prognosis in OCSCC, in particular for early-stage disease.